The Role and Importance of Internet Banking in the Modern Banking System - Nuriddinova Umida; Karimova Aziza Maxomadrizoevna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article discusses issues related to the role and importance of Internet banking in the modern banking system, discusses the concepts of subjects and objects of Internet banking and the principles of operation and creation of the system in modern banking conditions, the pros and cons of online banking.